A rare cause of cholestasis: Congenital right diaphragmatic hernia - Gülcü Taşkın, Didem; Emre, Şenol; Özmen, Evrim; Kepil, Nuray; Adaletli, İbrahim; Kutlu, Tufan; Cullu, Fugen; Erkan, Tulay; Senyuz, Osman (Journal of Surgery and Medicine, 2020)
An 82-day-old infant, investigated for sudden onset jaundice and acholic feces, was referred to our department, as no gallbladder was observed by abdominal ultrasonography. Her chest x-ray revealed an elevated right diaphragm, and the breath sounds were diminished on the right. Suspicious arteriovenous malformation in the fifth segment of the right lobe accompanied by a rotation anomaly of liver was reported. Tomography scans showed right diaphragmatic hernia where the left lobe of liver and gallbladder herniated to the thoracic space. In this case with right Bochdalek hernia, the bile ducts had kinked in the thoracic cavity, causing obstructive jaundice. If the kinking continues despite relocation of organs into the abdominal cavity, cholecystectomy-hepaticojejunostomy is an effective and reliable surgical method. Myriad pathologies may cause cholestasis, and surgical reasons should be investigated and diagnosed without delay to improve prognosis. For closure of the diaphragmatic defect, primary repair should be the preferred method. With this case, we wanted to emphasize a highly different presentation of Bochdalek hernia and remind that diaphragmatic hernia should be kept in mind in patients presenting with cholestasis and acholic stools.